The long multiphase trunk–tributary surge history of the high-Arctic Chapman Glacier, 1959–2023 - Wesley Van Wychen; Hester Jiskoot; Kristie Shannon; Carolyn Gorwill (Arctic, Antarctic, and Alpine Research)
Surge-type glaciers have been identified throughout the Canadian Arctic, but detailed surge behavior has been sparsely studied. Recent high spatiotemporal resolution satellite products enable such studies, allowing for better process-based understanding of surging in this region. Here, we present a multidecadal record (1999–2023) of flow velocities, strain rates, and elevation changes for Chapman Glacier, a 40-km-long land-terminating glacier on Umingmak Nuna (Ellesmere Island), using ITS_LIVE (Inter-mission Time Series of Land Ice Velocity and Elevation), Sentinel-1, and elevation time series data products. We further use historical remote sensing data to analyze surface morphology and displacement from 1959 to 2023. After an inferred century-long or longer quiescent phase, Chapman Glacier surged for at least twenty-two years in two successive phases. Phase 1 occurred from 2001 to 2012 and was spatially limited to the trunk, and Phase 2 started around 2012 and continues to 2024, impacting the main tributary and the lower part of the trunk. In each surge phase flow speeds increased from ~25 to >200 m a−1 over approximately ten years, propagated from up-glacier to down-glacier, and involved notable mass displacements. Our record of this high-Arctic surge and first account of a tributary–trunk surge in the Canadian Arctic contributes to the characterization of the spectrum of dynamic ice flow instabilities worldwide.